Virtual Community Mental Health Support during the COVID-19 Pandemic Crisis: Balancing Accessibility with Online Security. Issue 4 (1st September 2021) - Cypers, Scott Jared; Lopez, Amy
Abstract: The COVID-19 pandemic and subsequent quarantine orders led to a lot of uncertainty, fear, and mental health difficulty around the world. To be able to support the community during this time of crisis, especially when no in-person crisis services could be provided, an online mental health support and parenting group was offered to the community. While the primary goal of this group was to provide communitywide mental health support to as many parents as possible, the group was quickly compromised by people using the technology to disrupt the support program. The interference from disruptors to the security of the online program through so-called Zoombombing quickly created a dilemma as to how to safely provide quality care. This article provides a case report of a community-based parenting support program and explores the challenge of providing wide-scale online mental health care while also protecting the privacy and security of community members and the integrity of the program. In developing this project to support the community during the pandemic, several lessons were learned about use of virtual platforms, online security, and finding ways to care for the community through crisis.